Use of E. coli Purine Nucleoside Phosphorylase in the Treatment of Solid Tumors - Parker, William B.; Sorscher, Eric J. (Current Pharmaceutical Design, 2017)
Background: The selective expression of non-human genes in tumor tissue to activate non-toxic compounds (Gene Directed Enzyme Prodrug Therapy, GDEPT) is a novel strategy designed for killing tumor cells in patients with little or no systemic toxicity. Numerous non-human genes have been evaluated, but none have yet been successful in the clinic. Methods: Unlike human purine nucleoside phosphorylase (PNP), E. coli PNP accepts adenine containing nucleosides as substrates, and is therefore able to selectively activate non-toxic purine analogs in tumor tissue. Various in vitro and in vivo assays have been utilized to evaluate E. coli PNP as a potential activating enzyme. Results: We and others have demonstrated excellent in vitro and in vivo anti-tumor activity with various GDEPT strategies utilizing E. coli PNP to activate purine nucleoside analogs. A phase I clinical trial utilizing recombinant adenoviral vector for delivery of E. coli PNP to solid tumors followed by systemic administration of fludarabine phosphate (NCT01310179; IND# 14271) has recently been completed. In this trial, significant anti-tumor activity was demonstrated with negligible toxicity related to the therapy. The mechanism of cell kill (inhibition of RNA and protein synthesis) is distinct from all currently used anticancer drugs and all experimental compounds under development. The approach has demonstrated excellent ability to kill neighboring tumor cells that do not express E. coli PNP, is active against non-proliferating and proliferating tumors cells (as well as tumor stem cells, stroma), and is therefore very effective against solid tumors with a low growth fraction. Conclusion: The unique attributes distinguish this approach from other GDEPT strategies and are precisely those required to mediate significant improvements in antitumor therapy.
Keywords: GDEPT